The impact of the global economic and financial crisis on central, eastern and south-eastern Europe: A stock-taking exercise - Sándor Gardó; Reiner Martin (European Central Bank (ECB), 2010)
The paper first reviews the main drivers of the growth and real convergence process in central, eastern and south-eastern Europe (CESEE) since 2000 and assesses the key macro-financial strengths and vulnerabilities of the region at the beginning of the global economic and financial crisis. The main part of the paper reviews financial and real economic developments in these countries since the crisis started to impact the CESEE region. The paper finds that developments have been rather heterogeneous in the region. CESEE countries with the largest economic imbalances tended to be most affected. National and international support measures appear to have helped to stabilise financial markets, and parent banks of foreign bank subsidiaries in CESEE were committed to sustaining their exposure to the region. The degree to which CESEE governments were able to use policy instruments to counter the real effects of the crisis is rather heterogeneous, depending inter alia on the exchange rate regime in place and the initial fiscal positions.
Keywords: E52; E58; E44; 330; central; eastern and south-eastern Europe; financial crisis; vulnerability indicators; Finanzkrise; Internationale Konjunktur; Wirkungsanalyse; Ostmitteleuropa; Südosteuropa; EU-Staaten